2017
DOI: 10.1111/jfpp.13243
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of copper nanocomposite containing bilayer film for coconut oil packaging

Abstract: Copper nanocomposite containing edible bilayer pouch was fabricated from a heat sealable casein protein layer laminated with sodium alginate–pectin, and the developed pouch was used to package the coconut edible oil. The copper nanocomposite was synthesized by using heat treated and NaBH4 treated methods. The synthesized nanocomposites were incorporated in the bilayer film. Effect of incorporation of copper nanocomposite on mechanical, barrier, and antimicrobial properties of the film was then investigated. Ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…The antimicrobial property of lm containing heat treated CuO-NPs against the growth of E. coli were higher than the lm containing NaBH 4 -treated CuO-NPs. 10 Almasi, Jafarzadeh & Mehryar 11 found that CuO-NPs exhibit antibacterial act against Gram negative and Gram positive bacteria and that its inclusion in bacterial cellulose nanober reduced its antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial property of lm containing heat treated CuO-NPs against the growth of E. coli were higher than the lm containing NaBH 4 -treated CuO-NPs. 10 Almasi, Jafarzadeh & Mehryar 11 found that CuO-NPs exhibit antibacterial act against Gram negative and Gram positive bacteria and that its inclusion in bacterial cellulose nanober reduced its antibacterial activity.…”
Section: Introductionmentioning
confidence: 99%
“…This may attribute to the fact that both collagen and SA owing to their hydrophilic nature attract water molecules and create mobile regions with larger interchain distances. Additionally, these hydrophilic SA compete with water at the active sites of the polymer matrix causing water clustering which also forms microcavities in the network structure [43,44]. The absorbed water molecules modify the film matrix, leading to a less dense structure where chain terminals are relatively more mobile, thus increasing water vapor transmission rate [45].…”
Section: Water Vapor Permeability (Wvp)mentioning
confidence: 99%
“…This bilayer-structural material was made of an active electrospun fibers mat embedded by PHBV18 (18% valerate) and CuO-NPs, and coating onto a bottom layer of concentration molded PHBV3 (3% mol valerate). Gautam and Mishra [ 79 ] synthesized Cu-NPs material compositing edible bilayer pocket prepared by heat and NaBH 4 treated methods to form a heat-sealable casein protein layer laminated with sodium alginate-pectin.…”
Section: Inorganic and Metal Oxide Nanomaterials Applied In Food Pmentioning
confidence: 99%
“…However, the actual applications in real food samples were little. Gautam and Mishra synthesized copper-based nanocomposite incorporating a pectin layer to enhance its antimicrobial activities [ 79 ]. It was applied in packaging coconut oil and then the oxidative stability of oil was investigated during storage.…”
Section: Inorganic and Metal Oxide Nanomaterials Applied In Food Pmentioning
confidence: 99%